Stability of a viscous incompressible conducting liquid layer of a cylindrical shape in an inhomogeneous temperature field and a magnetic field of a vacuum arc current through it - Andrieieva, O.L.; Borts, B.V.; Vanzha, А.F.; Korotkova, I.М.; Tkachenko, V.I. (Вопросы атомной науки и техники, 2021)
Convective mass transfer in a cylindrical viscous incompressible conductive fluid layer in an inhomogeneous temperature field and in the external magnetic field of the vacuum arc current through it is theoretically investigated in this work. For a horizontal layer of a viscous, incompressible, conducting liquid of a cylindrical shape, located in a temperature field inhomogeneous in height and in an external magnetic field of a vacuum arc current flowing through it, the original equations are written. These equations consist of linearized equations for small velocity perturbations, small deviations from the equilibrium values of temperature, pressure, and magnetic field strength. The considered boundary value problem is solved for the case of free boundaries. Comparison of the experimental data with theoretical calculations made it possible to determine the rotation velocity of the steel melt during vacuum arc melting. Теоретично досліджений конвективний масоперенос в’язкої нестисливої провідної рідини циліндричної форми в неоднорідному полі температури і в зовнішньому магнітному полі струму вакуумної дуги, що протікає по ній. Записані вихідні рівняння для горизонтального шару в'язкої, нестисливої, провідної рідини циліндричної форми, що знаходиться в неоднорідному по висоті температурному полі і в магнітному полі струму вакуумної дуги, що протікає по ній. Ці рівняння складаються з лінеаризованих рівнянь для малих збурень швидкості, малих відхилень від рівноважних значень температури, тиску і напруженості магнітного поля. Вже згадана крайова задача вирішена для випадку вільних меж. Порівняння експериментальних даних з теоретичними розрахунками дозволило визначити швидкість обертання розплаву сталі при вакуумнодуговій плавці. Теоретически исследован конвективный массоперенос вязкой несжимаемой проводящей жидкости цилиндрической формы в неоднородном поле температуры и во внешнем магнитном поле протекающего по ней тока вакуумной дуги. Записаны исходные уравнения для горизонтального слоя вязкой, несжимаемой, проводящей жидкости цилиндрической формы, находящейся в неоднородном по высоте температурном поле и во внешнем магнитном поле протекающего по ней тока вакуумной дуги. Эти уравнения состоят из линеаризованных уравнений для малых возмущений скорости, малых отклонений от равновесных значений температуры, давления и напряженности магнитного поля. Рассматриваемая краевая задача решена для случая свободных границ. Сравнение экспериментальных данных с теоретическими расчетами позволило определить скорость вращения расплава стали при вакуумно-дуговой плавке.